Does This Adult Patient With Jolt Accentuation of Headache Have Acute Meningitis?. Issue 10 (4th September 2018) - Tamune, Hidetaka; Kuki, Takaie; Kashiyama, Tetsuya; Uchihara, Toshiki
Abstract: Objective: In order to identify appropriate candidates with suspected meningitis for lumbar puncture (LP), study designs and diagnostic values of jolt accentuation of headache (JA) were reviewed. Background: Acute meningitis is a life‐threatening disease that requires LP for accurate diagnosis. JA was reported the most sensitive indicator of cerebrospinal fluid pleocytosis; however, subsequent studies have failed to confirm this claim. Methods: We reviewed articles concerning JA, published prior to December 2017, using MEDLINE and Japanese medical databases. Seven original articles based on independent cohorts were eligible for inclusion and articles citing these 7 were thoroughly searched (11 in total). Additionally, all medical records of our previously reported cohort were reviewed again to explore how the patients' background influenced diagnostic values of JA. Results: We hypothesized that an oversimplified dichotomy of JA findings, pleocytosis, and meningitis created a misconception that JA is a universal indicator of meningitis. We clarify the difference between them and present altered mental status (AMS) as a key to decrease the sensitivity of JA. Notably, the sensitivity and specificity of JA were relatively low in unselected groups, while they tended to be high in the selected sub‐groups with acute onset of headache and fever, without AMS or neurological deficits. Unselected populations included etiologies of pleocytosis other than acute meningitis, which might weaken the association between JA and pleocytosis. Conclusion: JA is not a universal, stand‐alone, indicator of meningitis in febrile patients with headache. Therefore, we propose a stepwise approach for patients with suspected acute meningitis. AMS or neurological deficits suggest an intracranial pathology, which may necessitate a lumbar puncture. JA seems a useful tool for distinguishing acute aseptic meningitis from upper respiratory infection when used in the selected cohort of febrile patients (≥37°C) with recent‐onset headache (within 2 weeks before presentation) and normal mental status. This approach and diagnostic values of JA should be further investigated by prospective studies using operationally sorted candidates.